TATALAKSANA RECURRENT INTRA ORAL HERPES DISERTAI CANDIDIASIS YANG DIRUJUK OLEH DERMATOLOGIST - Raziv Ganesha; Dwi Setyaningtyas; Diah Savitri E; Priyo Hadi; Israyani (Interdental: Jurnal Kedokteran Gigi, 2020)
Introduction : Herpes simplex virus (HSV) is one variant of the herpes virus that infects humans, has two main types of HSV-1 that manifests more found in the mucosa of the mouth, pharynx, and skin (upper waist), and the type HSV-2 manifests in the genital area (lower waist). Case: 16-year-old female patient were referred from dermatologis RSAL Dr Ramelan Surabaya with complaints of many ulcers, whitish area of the tongue, palatum, vestibulum and genitals. Case Treatment: patients treated with systemic drugs of acyclovir, fluconazole, folic acid, vitamin B, vitamin C, methyl prednisolone, aloe vera extract topical. Patients were tested for blood, HSV-1 & HSV-2 (+), HIV (-), ANA (-). Discussion: Herpes simplex infection is a disease caused by the herpes simplex virus (HSV) which is a DNA virus (Deoxyribonucleic acid). In humans, the herpes virus can be latent and reactivate Reactivation can occur because of a trigger in the form of decreased immunity due to weather changes, fever, sun exposure, emotional stress, trauma, pregnancy, hormonal, systemic diseases, allergies, and immunosuppression. In this case the cause is thought to be due to hormonal. The diagnosis of primary HSV infection and recurrent infection is usually obtained from clinical features and laboratory tests are used establish the diagnosis. Conclucion: Recurrence of HSV infection can be reduced if avoid trigger factors. HSV infection management aimed at the control of pain, supportive treatment and definitive treatment. In this case, multidisciplinary collaboration is required in the treatment because it involves two sites, oral and genital. Keyword : HSV, Recurrent Herpes Oral, Oral Candidiasis